Overview of Critical Reflective Work Behavior in Nursing Profession Students - NI PUTU MULIA FERNANDA; Raini Diah Susanti; Theresia Eriyani (Journal of Nursing Care, 2022)
Informal learning in the work/practice environment can be seen through critical reflective work behaviour, namely a series of activities to optimize individual and group practice. This study aims to describe critically reflective work behaviour (CRWB) and its dimensions, namely individual CRWB, CRWB in social interaction, openness to new findings and cross-checking information on internship nursing students of the Faculty of Nursing, Universitas Padjadjaran. This research design is descriptive quantitative with a modified critically reflective work behaviour questionnaire instrument. The instrument test is a content test through expert judgment, face validity on 23 respondents with good test results, construct test (r = 0.41), and reliability test (Cronbach's Alpha = 0.765). The study population was internship nursing students from the Faculty of Nursing, Padjadjaran University (N=208). A total sampling technique did sampling with a response rate of 74.5% (n=155). Ethics permit number 513/UN6.KEP/EC/2021 from the Research Ethics Commission of Padjadjaran University Bandung. The results showed that the nursing profession students of the Faculty of Nursing, Universitas Padjadjaran, tend to have high PKRK (56.1%). Social interaction is in the moderate category (69%). When viewed on each dimension, high results were also obtained on the individual CRWB dimension (77.4%), the openness dimension to new findings (56.8%), and the information cross-check dimension (72.9%). A high CRWB shows that students can adapt to changing circumstances and construct knowledge actively and personally. Suggestion: It pays attention to the peer evaluation method because it relates to the CRWB dimensions in social interactions, including sharing critical opinions, asking for input from others, challenging group thinking, and being open about one's mistakes.